How depressive symptoms and fear of negative evaluation affect feedback evaluation in social decision-making - Weiß, Martin; Rodrigues, Johannes; Boschet, Juliane M.; Pittig, Andre; Mussel, Patrick; Hewig, Johannes (Journal of Affective Disorders, 2020)
Background The influence of emotional feedback on social decision-making situations is an omnipresent part of social interaction. Complementing existing research on the impact of approach- and avoidance-related personality traits, we examined the role of sub-clinical depression and fear of negative social evaluation in a modified ultimatum game. Methods Different proposer identities reacted with distinct affective facial expressions to the acceptance and rejection of monetary offers in the ultimatum game. Facial expressions of proposers were relevant for depression and anxiety: A smile in response to acceptance or angry and sad feedback in response to rejection. Results People with higher symptoms of depression rejected more offers when the offer magnitude increased. Both, individuals with symptoms of depression and fear of negative evaluation approached sad feedback by rejecting more offers. At the neural level, positive emotional feedback (i.e., a smiling face) was linked to a reward positivity, which did not occur in participants with higher symptoms of depression. Limitations Since our paradigm implies a decision-dependent feedback pattern, the negative feedback might have been expected and was therefore not perceived as particularly relevant. Conclusions The results indicate specific behavioral as well as neural reaction patterns, which can be used especially for an initial subclinical identification of depression.
Keywords: Emotional feedback; Fear of negative evaluation; Depression; Ultimatum game; Reward processing